2022
DOI: 10.36129/jog.2022.25
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of a 13 weeks viable ectopic cesarean section Scar pregnancy: a case report

Abstract: Background. Cesarean scar ectopic pregnancy is a rare type of life-threatening pregnancy whereby the embryo implants on a uterine scar, due to a previous cesarean section. It accounts for about 4.2% of total ectopic pregnancies. It is very rare that an ectopic scar pregnancy arrives undetected up to 13 weeks, but this is the case of some patients, not regularly scanned during the early pregnancy. The objective of our case report is to present a novel conservative laparoscopic approach in such cases. Case prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…No data are available on the fertility and reproductive outcome according to M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n different managements for twin cervical pregnancies. There is no consensus on the best management in cases of ectopic pregnancies; recent evidence have shown that scar pregnancies can benefit from a laparoscopic approach [31], and also in cases of heterotopic pregnancies, the laparoscopic treatment is safe for both the woman and the in-utero pregnancy [32,33]. Data from literature showed that, in cases of tubal ectopic pregnancies, expectant management may have better reproductive outcomes compared to women who underwent surgery, with the shortest time to achieve a subsequent intrauterine clinical pregnancy [34,35].…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%
“…No data are available on the fertility and reproductive outcome according to M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n different managements for twin cervical pregnancies. There is no consensus on the best management in cases of ectopic pregnancies; recent evidence have shown that scar pregnancies can benefit from a laparoscopic approach [31], and also in cases of heterotopic pregnancies, the laparoscopic treatment is safe for both the woman and the in-utero pregnancy [32,33]. Data from literature showed that, in cases of tubal ectopic pregnancies, expectant management may have better reproductive outcomes compared to women who underwent surgery, with the shortest time to achieve a subsequent intrauterine clinical pregnancy [34,35].…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%